Impact of Digoxin on Endocrine Glands in Male Rats - Abbas A. Khudhair 1 , Kassim F. Abdulkareem2 , Muhsin S.G. Al_Mozie’l 3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study is performed to provide the pathological changes of thyroid gland, pancreas and adrenal glandthat occurred due to exposure to the digoxin drug. The study uses twenty four adult male rat randomlydivided into 3 equal groups as follows: G1 control group treated with distilled water, G2 dosed with 0.3mg/kg digoxin and G3 dosed with 0.9mg/kg digoxin given orally by gavage daily for 60 days. All animals weresacrificed at the end of experiment and organs were collected in 10% buffered formalin for histopathologicalevaluation. Result reveals dilation of thyroid follicles with flattened follicular epithelium which increasewith high dose group digoxin in comparison with control. Adrenal gland showed moderate atrophy ofcortical layers especially zona reticularis with hyperplasia of medulla cells probably of digoxin like ouabainproducing cells, on the other hands pancreas doesn’t reveal remarkable changes except congestion of vesselsin high dose group compared to control.